2020
DOI: 10.1186/s12934-020-01300-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous caffeic acid biosynthesis in Escherichia coli is affected by choice of tyrosine ammonia lyase and redox partners for bacterial Cytochrome P450

Abstract: Background: Caffeic acid is industrially recognized for its antioxidant activity and therefore its potential to be used as an anti-inflammatory, anticancer, antiviral, antidiabetic and antidepressive agent. It is traditionally isolated from lignified plant material under energy-intensive and harsh chemical extraction conditions. However, over the last decade bottom-up biosynthesis approaches in microbial cell factories have been established, that have the potential to allow for a more tailored and sustainable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…The analysis of the methanolic extract led to the isolation of several components, in particular arzanol, a characteristic and novel pholoroglucinol α -pyrone isolated from Helichrysum spp., which possesses a variety of pharmacological activities including acting as an eicosanoid inhibitor on PGE 2 synthesis and the NF-κB pathway. Moreover, it has other important constituents including caffeic and quercetin derivates, which possess strong antioxidant and anti-inflammatory activities and they have been reported to have beneficial effects on mood disorders [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the methanolic extract led to the isolation of several components, in particular arzanol, a characteristic and novel pholoroglucinol α -pyrone isolated from Helichrysum spp., which possesses a variety of pharmacological activities including acting as an eicosanoid inhibitor on PGE 2 synthesis and the NF-κB pathway. Moreover, it has other important constituents including caffeic and quercetin derivates, which possess strong antioxidant and anti-inflammatory activities and they have been reported to have beneficial effects on mood disorders [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The co-localization of β-carotene ketolase and β-carotene hydroxylase on the membrane, via their fusion by the glycerol uptake facilitator protein, resulted in a 2.2-fold improvement in the astaxanthin yield [ 42 ]. The protein scaffold strategy using heterotrimeric DNA sliding clamp PCNA (Proliferating Cell Nuclear Antigen) of Sulfolobus solfataricus P2 was also utilized to improve the activity of cytochrome P450 enzyme on the production of caffeic acid [ 43 ].…”
Section: Protein Scaffoldsmentioning
confidence: 99%
“…In the recent methods that have been developed for the sustainable production of phenylpropanoids in recombinant E. coli , FjTAL has been proposed as one of the potential enzymes to convert L-tyrosine to p-coumaric acid 1 2 (Fig.1). Although it has been demonstrated that Flavobacterium johnsoniae Tyrosine Ammonia Lyase (FjTAL), has satisfactory affinity for L-tyrosine (K m ∼ 6.7 μM), little has been reported on the binding affinity of other structurally-related metabolites to FjTAL 3 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that Flavobacterium johnsoniae Tyrosine Ammonia Lyase (FjTAL), has satisfactory affinity for L-tyrosine (Km ~ 6.7 μM), little has been reported on the binding affinity of other structurally-related metabolites to FjTAL 3 4 . It has been hypothesized by Sariaslani 5 (2007) and Haslinger and Prather (2020) that p-coumaric acid, the product of elimination reaction catalyzed by FjTAL, might inhibit the activity of the enzyme, exerting a kind of negative feedback response. Our goal in this study, was to computationally predict the 3D structure of FjTAL, paving the way to help other researchers to reasonably engineer the protein for the future studies.…”
Section: Introductionmentioning
confidence: 99%